2020
DOI: 10.1136/openhrt-2019-001120
|View full text |Cite
|
Sign up to set email alerts
|

Needs analysis of parents following sudden cardiac death in the young

Abstract: ObjectiveThe sudden cardiac death (SCD) of a young person is a devastating event for any parent. Inherited heart disease is often either identified or assumed to be the cause. Few studies have explored the psychosocial impact to the surviving at-risk family members. We sought to investigate the needs of parents who have experienced the SCD of their child (≤45 years).MethodsA quantitative needs analysis questionnaire was developed based on semistructured interviews, including one focus group and a review of rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
(18 reference statements)
2
13
0
Order By: Relevance
“…First, our results are broadly in line with general observations about the devastating impact of the sudden loss of a child and resulting support needs. 8 As regards the specific challenges of YSCD, our results concur with the recent needs analysis by McDonald et al., 10 which identified needs for instrumental support in the form of a safe place to turn to and emotional support through affiliation and informational input. This is reflected in Theme 1 (YSCD community support as offering a place of safety).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…First, our results are broadly in line with general observations about the devastating impact of the sudden loss of a child and resulting support needs. 8 As regards the specific challenges of YSCD, our results concur with the recent needs analysis by McDonald et al., 10 which identified needs for instrumental support in the form of a safe place to turn to and emotional support through affiliation and informational input. This is reflected in Theme 1 (YSCD community support as offering a place of safety).…”
Section: Discussionsupporting
confidence: 90%
“…McDonald et al. 10 observed that the need for medical information and for understanding the cause of the death constituted the most significant need in families and was mostly unmet. Our study showed that making sense of the death was not only about medical explanations but about meaning-making at a broader level, reflecting definitions of sense-making and meaning-making in the literature on trauma and bereavement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent needs analysis of parents who had experienced the SCD of their child (including adult children) found that while medical information and support were the most important need, psychological information and support were the most unmet need. 126 Nearly threequarters reported wanting access to professional counseling or psychological services. Further, many indicated access to genetic testing or understanding the genetic cause to be an important need, highlighting the importance of maintaining realistic expectations regarding the diagnostic yield of postmortem genetic testing with families.…”
Section: Provide Psychosocial Support and Identify When Referral To Clinical Psychologist Is Requiredmentioning
confidence: 99%
“…A recent needs analysis of parents who had experienced the SCD of their child (including adult children) found that while medical information and support were the most important need, psychological information and support were the most unmet need 126 . Nearly three‐quarters reported wanting access to professional counseling or psychological services.…”
Section: Psychological Carementioning
confidence: 99%